Experimentalist governance: low-carbon transition in China - Zhuohan, Xie (The University of Edinburgh, 2025)
China’s low-carbon transition has been characterised by large-scale policy experimentation. However, existing theoretical frameworks such as Chinese experimentalism, experimentalist governance, socio-technical transitions, and institutional theory each emphasise particular aspects of innovation, system change, or institutional evolution, but none alone adequately capture the multi-level, cross-system and uncertain dynamics of China’s governance environment. To address this gap, the thesis develops what it calls the Low-Carbon Experimentalist Governance (LCEG) framework. This framework is proposed on the basis of extensive documentary analysis and more than 150 interviews across three empirical cases, and it is conceptually grounded in three strands of literature: governance experimentation, socio-technical transition, and institutional change. The LCEG framework integrates and extends these perspectives to provide a novel analytical tool for explaining how China’s low-carbon experimentation drives multi-actor interaction, institutional restructuring, and systemic change. The research adopts a case study design, drawing on three empirical cases: the Low-Carbon City Pilot Programme (LCCP), the Zhangjiakou wind-power heating experiment, and the Henan provincial rooftop distributed PV pilot programme. The study combines documentary analysis with more than 150 semi-structured interviews with policymakers, enterprises, experts and other stakeholders across multiple levels, thereby creating a robust empirical foundation. Drawing on both the theoretical foundations outlined above and the empirical evidence gathered in this study, the findings demonstrate that China’s low-carbon experimentation can be explained through the three levels of the LCEG framework. First, multi-actor interactions shape experimental trajectories within institutional gaps, where social capital and guanxi, understood as informal interpersonal networks and reciprocal ties that influence trust and resource exchange, play a double-edged role. Second, evolutionary mechanisms of experimental pathways operate through two dimensions: (2a) cross-system coordination, which couples’ policy pilots with energy markets but also generates fragmentation and conflict; and (2b) institutional reconfiguration, which takes the form of gradual transformation that reshapes the relationships among local SOEs, grid companies and governments. Third, learning and feedback mechanisms are both selective and path-dependent: successful practices are absorbed into policy, while shortcomings also generate corrective reforms. The thesis makes four main contributions. First, in response to Gap 1, defined as the limited theorisation of public–private interaction in Chinese experimentalism, it develops the LCEG framework as an integrative analytical perspective, overcoming the limitations of single theories such as Chinese experimentalism, experimentalist governance, socio-technical transition theory and institutional theory, and providing a more comprehensive explanation of China’s low-carbon transition. Second, in response to Gap 2, it identifies the critical role of cross-system coordination in shaping China’s low-carbon governance. Third, in response to Gap 3, it explains the dynamic relationship between experimentation and institutional reconfiguration. Fourth, in response to Gap 4, it highlights the selective and path-dependent nature of learning and feedback. Overall, the thesis’s core contribution lies in the development of the LCEG framework, which deepens understanding of China’s low-carbon transition and offers new theoretical insights for international debates on experimentalist governance and institutional change.
Keywords: Experimentalist Governance; Low-Carbon Transition; China; LCEG Framework (Low-Carbon Experimentalist Governance); Socio-Technical Transition